Association between lifestyle and musculoskeletal pain: Cross-sectional study among 10,000 adults from the general working population - Kirsch Micheletti, Jéssica [UNESP]; Bláfoss, Rúni; Sundstrup, Emil; Bay, Hans; Pastre, Carlos Marcelo [UNESP]; Andersen, Lars Louis (Springer Nature, 2019)
Background: Work-related musculoskeletal pain is a major cause of work disability and sickness absence. While pain is a multifactorial phenomenon being influenced by work as well as lifestyle, less is known about the association between specific lifestyle factors and the type of musculoskeletal pain. The aim of the study was to investigate if a dose-response association existed between lifestyle factors and musculoskeletal pain intensity in the low back and neck-shoulder. Methods: Currently employed wage earners (N = 10,427) replied in 2010 to questions about work environment, lifestyle and health. Logistic regression analyses adjusted for various confounders tested the association of alcohol intake, physical activity, fruit and vegetable intake, and smoking (explanatory variables) with low back pain and neck-shoulder pain intensity (outcomes variables, scale 0-9, where ≥4 is high pain). Results: The minimally adjusted model found that physical activity and fruit and vegetable intake were associated with lower risk of musculoskeletal pain, while smoking was associated with higher risk of musculoskeletal pain. In the fully adjusted model, physical activity ≥5 h per week was associated with lower risk of low back pain and neck-shoulder pain with risk ratios (RR) of 0.95 (95% CI 0.90-1.00) and 0.90 (95% CI 0.82-0.99), respectively. No association was found between alcohol intake and pain. Conclusion: Being physically active associated with lower risk of having musculoskeletal pain, while smoking habits and healthy eating were associated with higher pain when adjusting for age and gender. Considering the continuously increasing retirement age in many societies, initiatives to promote healthy habits should still be a political priority to help the workers to stay healthy and cope to their work.
Keywords: Exercise, health, smoking; Low back pain; Musculoskeletal diseases, chronic pain; Neck pain